Johnson's New Brunswick, Nova Scotia, Newfoundland and Prince Edward Island. - Johnson, A. J. (Alvin Jewett), 1827-1884 (A.J. Johnson, 1866)
Map shows late nineteenth century railroads, cities, political divisions within each province in New Brunswick, Nova Scotia, Newfoundland and Prince Edward Island. Relief shown by hachures. Scale not given.